The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/1516-3180.2022.0513.r1.09022023
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in COVID-19 patients receiving mechanical ventilation: A cross-sectional study

Abstract: BACKGROUND: Coronavirus disease 2019 (COVID-19) can damage cardiac tissue by increasing troponin levels and inducing arrhythmias, myocarditis, and acute coronary syndrome. OBJECTIVES: To analyze the impact of COVID-19 on cardiac autonomic control in mechanically ventilated intensive care unit (ICU) patients. DESIGN AND SETTING: This cross-sectional analytical study of ICU patients of both sexes receiving mechanical ventilation was conducted in a tertiary hospital. METHODS: Patients were divided into COVID-19-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We suggest that SURVs within the COVID-19 group might have more powerful internal regulatory resources to limit the progress of inflammation, prevent exaggerated immune responses and avoid the development of arrhythmic events [1,8,11,12,22,49,51]. The more limited activity of the cardiac arm of the baroreflex might contribute to the worse prognosis associated with small HP variations in critically ill COVID-19 patients [1,7,8,19,20].…”
Section: Association Of Baroreflex Control Markers Of Non-covid-19 An...mentioning
confidence: 92%
See 2 more Smart Citations
“…We suggest that SURVs within the COVID-19 group might have more powerful internal regulatory resources to limit the progress of inflammation, prevent exaggerated immune responses and avoid the development of arrhythmic events [1,8,11,12,22,49,51]. The more limited activity of the cardiac arm of the baroreflex might contribute to the worse prognosis associated with small HP variations in critically ill COVID-19 patients [1,7,8,19,20].…”
Section: Association Of Baroreflex Control Markers Of Non-covid-19 An...mentioning
confidence: 92%
“…Modifications of the autonomic control and baroreflex function following COVID-19 infection have often been studied via the analysis of spontaneous changes in heart period (HP) and systolic arterial pressure (SAP) [17,18]. Remarkably, it was found that the magnitude of HP changes holds prognostic value in critically ill COVID-19 patients [1,7,8,19,20]. Lower values of HP variability were associated with the severity of COVID-19 [19], while higher values were a distinctive feature of surviving COVID-19 patients admitted to the ICU [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation